2009
DOI: 10.21236/ada501252
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Miter Gates

Abstract: This report presents results of a three-dimensional (3-D) finite element analysis of a generic miter gate with multiple cracks used to calculate the stress intensity factor using the J-integral approach. The model was also used to determine the optimum diagonals prestressing. Stress intensity factors and J-integral approach were validated numerically against closed-form solutions of semi-infinite plates with throughthickness cracks, double-edged cracks, single-edged crack, and cracks growing from round holes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Most important is that gaps have been found to be one of the primary causes for increased stress in fatigue-prone regions. [11] The higher stresses can be problematic, especially in the pintle region, which provides a nonredundant boundary condition for the gate. Increasing the stress range in fatigueprone components will reduce the fatigue life of the component, which could result in a shortened useful life of the gate if the component is not repaired or replaced in a timely manner.…”
Section: Selection Of Damage-sensitive Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Most important is that gaps have been found to be one of the primary causes for increased stress in fatigue-prone regions. [11] The higher stresses can be problematic, especially in the pintle region, which provides a nonredundant boundary condition for the gate. Increasing the stress range in fatigueprone components will reduce the fatigue life of the component, which could result in a shortened useful life of the gate if the component is not repaired or replaced in a timely manner.…”
Section: Selection Of Damage-sensitive Featurementioning
confidence: 99%
“…The gap seen in Figure is suspected to have been caused by an impact. Most important is that gaps have been found to be one of the primary causes for increased stress in fatigue‐prone regions . The higher stresses can be problematic, especially in the pintle region, which provides a nonredundant boundary condition for the gate.…”
Section: Selection Of Damage‐sensitive Featurementioning
confidence: 99%
“…Quoin block deterioration analysis conducted by [10] demonstrated that deterioration in the quoin block ( Figure 3) could drastically affect the state of stresses on the element transferring loads to the pintle and the pintle connection.…”
Section: Deterioration Examples Of Steel Hydraulic Structuresmentioning
confidence: 99%
“…Most of the failures of HSS are due to fatigue cracking. Welded connections with low fatigue resistance (Markland Lock, and Greenup), poor weld quality, unanticipated structural behavior, or unexpected loading due to the deterioration of the design boundary conditions (Riveros 2009) are the causes of fatigue cracking. The poor performance has led to miter gate investigations and repairs.…”
Section: Introductionmentioning
confidence: 99%